Pengaruh Implementasi Prinsip Good Corporate Governance terhadap Pencegahan Tindak Pidana Korporasi (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
This study explores the effect of the implementation of Good Corporate Governance (GCG) principles on the prevention of corporate crime in Indonesia. GCG, which consists of the principles of transparency, accountability, independence, responsibility, and fairness, plays an important role in preventing abuse of power, manipulation of financial statements, and other criminal offenses. Case studies on PT Asuransi Jiwasraya and PT Garuda Indonesia show how the weak implementation of GCG principles can open opportunities for corporate crime, which harms the state and stakeholders. Using a normative approach and legal analysis, this research highlights weaknesses in internal control, non-compliance with regulations, and limited competence of human resources as factors inhibiting the implementation of GCG. The research offers strategic recommendations to strengthen GCG implementation, such as enhancing ethical culture within the organization, strengthening regulations and sanctions, and providing continuous training for company management. The findings are expected to contribute to the development of better and more effective corporate governance in preventing corporate crime, as well as creating a business environment with integrity and sustainability.